INSTRUMEN DETEKSI DINI MANDIRI BERBASIS TELENURSING UNTUK RISIKO ULKUS KAKI DIABETES: LITERATURE REVIEW - Ratna Wirawati Rosyida; Sugiyarto (Rena Cipta Mandiri, 2025)
Background: Diabetic ulcers are a complication of diabetes that has a physical, mental, and economic impact on patients. Telenursing can help in the early detection process to prevent complications. Aim: to review the literature on the application of telenursing-based instruments for early detection of the risk of diabetic ulcers. Methods: literature study through PubMed, ScienceDirect, and manual search using the keywords diabetes mellitus AND foot screening AND diabetic foot ulcer. The search process follows PRISMA rules. Results: Obtained 6 articles. from several countries, namely China (n=2), the United Kingdom (n=1), Spain (n=1), Indonesia (n=1), and does not explain the country of origin (n=1). The instruments developed are questionnaires that can be used by health workers or patients independently (n=4), in the form of a smartphone application (n=1), and in the form of an automatic learning machine (n=1). All instruments that have been developed are valid and reliable and have high sensitivity and specificity for screening the risk of diabetic ulcers. In addition, there is an instrument questionnaire that requires users to understand how to check the function of foot sensations using a 10-g monofilament or the Ipswich Touch method. Conclusion: There have been various types of instruments for early detection of the risk of diabetic ulcers that allow patients to carry out early detection independently. In addition, the existing instruments are easy to use and do not require any special training.